The antineoplastic drug flavopiridol reverses memory impairment induced by Amyloid-ß1-42 oligomers in mice. (April 2016) - Leggio, Gian Marco; Catania, Maria Vincenza; Puzzo, Daniela; Spatuzza, Michela; Pellitteri, Rosalia; Gulisano, Walter; Torrisi, Sebastiano Alfio; Giurdanella, Giovanni; Piazza, Cateno; Impellizzeri, Agata Rita; Gozzo, Lucia; Navarria, Andrea; et al.
Graphical abstract: Abstract: The ectopic re-activation of cell cycle in neurons is an early event in the pathogenesis of Alzheimer's disease (AD), which could lead to synaptic failure and ensuing cognitive deficits before frank neuronal death. Cytostatic drugs that act as cyclin-dependent kinase (CDK) inhibitors have been poorly investigated in animal models of AD. In the present study, we examined the effects of flavopiridol, an inhibitor of CDKs currently used as antineoplastic drug, against cell cycle reactivation and memory loss induced by intracerebroventricular injection of Aß1-42 oligomers in CD1 mice. Cycling neurons, scored as NeuN-positive cells expressing cyclin A, were found both in the frontal cortex and in the hippocampus of Aβ-injected mice, paralleling memory deficits. Starting from three days after Aβ injection, flavopiridol (0.5, 1 and 3 mg/kg) was intraperitoneally injected daily, for eleven days. Here we show that a treatment with flavopiridol (0.5 and 1 mg/kg) was able to rescue the loss of memory induced by Aβ1-42, and to prevent the occurrence of ectopic cell-cycle events in the mouse frontal cortex and hippocampus. This is the first evidence that a cytostatic drug can prevent cognitive deficits in a non-transgenic animal model of AD.